Propolis reduces Leishmania amazonensis-induced inflammation in the liver of BALB/c mice - da Silva, Suelen S. (2016)
Experimental models of mouse paw infection with L. amazonensis show an induction of a strong inflammatory response in the skin, and parasitic migration may occur to secondary organs with consequent tissue injury. There are few studies focusing on the resolution of damage in secondary organs caused by Leishmania species-related cutaneous leishmaniasis. We investigated the propolis treatment effect on liver inflammation induced by Leishmania amazonensis infection in the mouse paw. BALB/c mice were infected in the hind paw with L. amazonensis (107) promastigote forms. After 15 days, animals were treated daily with propolis (5 mg/kg), Glucantime (10 mg/kg), or with propolis plus Glucantime combined. After 60 days, mice were euthanized and livers were collected for inflammatory process analysis. Liver microscopic analysis showed that propolis reduced the inflammatory process compared to untreated infected control. There was a decrease of liver myeloperoxidase and N-acetyl-β-glucosaminidase activity levels, collagen fiber deposition, pro-inflammatory cytokine production, and plasma aspartate transaminase and alanine transaminase levels. Furthermore, propolis treatment enhanced anti-inflammatory cytokine levels and reversed hepatosplenomegaly. Our data demonstrated that daily low doses of Brazilian propolis reduced the secondary chronic inflammatory process in the liver caused by L. amazonensis subcutaneous infection in a susceptible mice strain.